"Down with 1989!": The Peculiar Right-Wing Backlash against 1968 in Poland. Issue 4 (November 2019) - Ost, David
This article is part of the special cluster titled Generation '68 in Poland (with a Czechoslovak Comparative Perspective). Whereas much of the European right greeted the fiftieth anniversary of 1968 with a critique of its legacy, Poland's ruling Law and Justice party was largely silent, both because 1968 did not usher in a counterculture and because the protests were directed against the communist party. And yet the Law and Justice party detests the legacy of 1968, for three reasons: 1968 was shaped by the left, '68 activists and their values played a key role in the ensuing opposition, and because the right actually sympathizes with the communists of 1968, then dominated by nationalists. The right thus traditionally attacks the legacy of 1968 by attacking 1989 instead, when '68' ers played a central role and new left progressivism could finally emerge. That began changing early in 2018 when Poland's parliament passed its Holocaust-speech law banning calumny against the "Polish Nation." The resulting criticism brought 1968 back with a vengeance, with the right openly inhabiting the role of the national-communists, and beginning to attack Poland's 1968 directly. Shedding new light on the diverse meanings of 1968 and the relationship of the right to national communism, the piece ends by looking at developments through Bernhard and Kubik's theory of the politics of memory.